Naphthalene Acetic Acid Mitigates the Adverse Effects of Climate Change on Rice Productivity and Grain Quality under Different Nitrogen Fertilizer Levels: Rice production and agronomic performance - Gharieb, Abdelfatah; Elsaka, Mai; Elsayed, Ghada (ORYZA-An International Journal of Rice, 2026)
Rice productivity in Egypt is increasingly constrained by rising temperatures, limited resources, and the need to improve nitrogen-use efficiency (NUE). Although 1-naphthaleneacetic acid (NAA) can enhance crop growth and nutrient utilization, its interaction with nitrogen fertilization in newly released Egyptian rice cultivars remains poorly understood. Therefore, a field experiment was conducted to evaluate the effects of nitrogen fertilization and foliar NAA application on productivity, grain quality, nutrient accumulation, and NUE of the rice cultivar Giza 184 under transplanted conditions following barley. The experiment was arranged in a split-plot design with four replications, comprising four nitrogen rates (0, 55, 110, and 165 kg N ha-1) and four NAA concentrations (0, 5, 10, and 15 ppm). NAA was sprayed at 25 and 55 days after transplanting. Nitrogen and NAA significantly improved growth, yield attributes, grain quality, and nutrient concentrations (N, P, K, and Zn) in grain and straw. The combined application of 165 kg N ha-1 and 15 ppm NAA produced the highest grain yields (11.61 and 11.80 t ha-1) and straw yields (17.83 and 17.92 t ha-1) during 2024 and 2025, respectively. This treatment also enhanced milling quality and nutrient accumulation, with grain phosphorus concentration reaching 0.214% and 0.213% and straw potassium concentration reaching 2.41% and 2.63% in the respective years. However, the highest NUE was achieved at 110 kg N ha-1 combined with 10-15 ppm NAA. Integrating NAA with nitrogen fertilization can therefore improve rice productivity, grain quality, nutrient enrichment, and NUE, contributing to more sustainable rice production in Egypt.